Finite Element Analysis of Hysteretic Behavior of Superposed Shear Walls Based on OpenSEES - Shaole Yu; Yujian Zhang; Junhao Bie; Wenying Zhang; Jialei Jiang; Hua Chen; Xinxi Chen (Buildings, 2023)
The superimposed slab shear wall has been found to be more and more applicable in the building construction industry due to its building industrialization superiority. The hysteretic behavior of superimposed slab shear walls accounts for an important part of seismic performance analysis. This paper presents the results of a numerical study to investigate the hysteretic behavior of superimposed slab shear walls. Different calculation methods of the shear capacity of the combined interface and horizontal connection are introduced. The calculated results show that the shear capacity of the combined interface and horizontal connection is much larger than the ultimate shear capacity of a superimposed slab shear wall. Therefore, the bond slip effect of a combined interface and horizontal connection can be ignored in finite element analysis on the premise of it not affecting calculation precision. Three different theoretical analysis models, namely the vertical multi-line element model, bend–shear coupled fiber model and layered shell element model, were established in OpenSEES based on a macro-model and a micro-model. The results show that the calculated results of the vertical multi-line element model and the bend–shear coupled fiber model agree reasonably with the experiment results, whereas the calculated results of the layered shell model gave a relatively larger initial stiffness.